Study of Diabetes Mellitus Management Policies Using a Systems Approach in Surge Capacity - Badriah, Siti; Cahyati, Peni; Nurcahyani, Lia; Iman, Arief Tarmansyah; Ristrini, Ristrini; Astuti, Athanasia Budi (JKG (JURNAL KEPERAWATAN GLOBAL), 2023)
Background: The prevalence of Diabetes Mellitus (DM) in Indonesia continues to increase, even though DM control policies and programs have been implemented. According to existing policies, the family has not been involved in diabetes control. This study evaluates diabetes mellitus management policies by designing family-based community empowerment model interventions with a systems approach to surge capacity.   Methods: The design of this study used a cross-sectional operational analysis conducted in Cirebon City with 26 participants. Data collection was carried out using Focus Group Discussion (FGD) and in-depth interviews using interview guidelines from the surge capacity component. Inclusion criteria were Non-Communicable Diseases program holders at the Cirebon City Health Office and Community Health Centers with the highest and lowest prevalence, and DM sufferers and their families representing each age and gender category. Data analysis was performed using open code.   Results: The non-communicable disease program has not been integrated between the health office and the hospital; funds for the DM prevention program have not met the needs; there are limited human resources with multiple tasks and an excessive workload, so it is not optimal for DM health services; and there is a lack of family involvement in diabetes control, so the incidence of DM is still not usually controlled.   Conclusion: Policy studies using a system approach in surge capacity have been able to dig up various information on DM control efforts in terms of policy, organizational structure, DM surveillance, information systems, integrated services, case screening, budgeting, and community empowerment.